Realignment expectations in the ERM: Causes and measurement - Sinimaaria Ranki (Bank of Finland, 1996)
The purpose of this study is to analyze realignment expectations in the exchange rate mechanism of the European Monetary System (EMS), in particular with reference to the five year period (1987-1992) during which no realignments were done.The period chosen for this study provides us an interesting sample in this respect, because, in mid-1990, the EMS faced a historical asymmetric shock of German Monetary Unification (GMU).Dramatic changes in the fundamentals of the anchor country of the system can help us to detect channels through which macroeconomic developments affect the pressure to realign and, therefore, expectations of such realignments. By using a model that breaks the interest rate differential in two components, the expected rate of depreciation within the allowed fluctuation band and the expected rate of depreciation of the central parity rate, we get a measure for the credibility of the exchange rate.We estimate the expected rate of depreciation of the exchange rate within the band, subtract the results from the interest rate differential and obtain values for the expected rate of devaluation.Finally, the estimated values for the expected rate of devaluation are regressed on selected macroeconomic variables in order to find out to which extent the expected rate of devaluation depends on economic fundamentals.The model was built by including the commonly most important factors for exchange rate determination. We observed increased exchange rate credibility in the form of decreasing devaluation expectations over the period 1987-1992.The explanation for this increase in the stability of the EMS is that German interest rates and inflation, were moving upwards and hence, approaching the corresponding variables of the other EMS countries. It was the convergence of these variables that eased the pressure on the nominal exchange rates.Therefore, signs of the 1992 crisis could not be seen in advance in expectations. Our results emphasize the role of the relative cyclical positions of the pegging countries vis-à-vis the anchor country of the system.Thus, expectations of possible realignments as a means of adjustment became actual first after it could be seen that there was a discrepancy between the cyclical needs of the economies in the other EMS countries and the high interest rates imposed on the ERM by Germany.These discrepancies became visible first in the traditional weak-currency countries that faced the most difficult domestic economic situation.This is mirrored by the fact that for these countries the government deficit, relative to Germany, clearly affected devaluation expectations.The divergence of the business cycles added to this effect.The level of foreign exchange reserves of the central bank was observed by the markets, which indicates the praneness of these currencies to get under a speculative attack.In the hard-currency countries, by contrast, devaluation expectations could not be seen even in the very eve of the crisis.For these countries, we obtained the inverse result that a growing government domestic deficit as compared to Germany tends to strengthen the currency of the home country.Markets also seem to observe the inflation rate differential.For the crisis, however, this factor could not play a crucial role because the inflation rates of the hard-currency countries were practically at the German inflation rate level.All in all, the results of this study suggest that the crisis was due to the reversal in the German business cycle in a situation where the anchor country conducted a strict monetary policy to fight domestic inflation pressures.
URN:NBN:fi:bof-201408071711
Keywords: 330; Exchange Rate Mechanism; target zone; devaluation expectations; exchange rates; German Monetary Unification